2009
DOI: 10.1007/s00586-009-1215-2
|View full text |Cite
|
Sign up to set email alerts
|

Is insufficient quantity and quality of sleep a risk factor for neck, shoulder and low back pain? A longitudinal study among adolescents

Abstract: The quantity and quality of adolescents' sleep may have changed due to new technologies. At the same time, the prevalence of neck, shoulder and low back pain has increased. However, only a few studies have investigated insufficient quantity and quality of sleep as possible risk factors for musculoskeletal pain among adolescents. The aim of the study was to assess whether insufficient quantity and quality of sleep are risk factors for neck (NP), shoulder (SP) and low back pain (LBP). A 2-year followup survey am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
2
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 54 publications
8
110
2
10
Order By: Relevance
“…Overall, 10 findings were reported, with 2 findings 34,38 showing that children with poor sleep quality are significantly at higher risk (both findings in the direction of poor sleep quality predictive of musculoskeletal pain), one finding 31 showing mixed evidence, and seven findings 31,[35][36][37]39,40 showing no significant higher risk (please see Table 4 for a full description of effect sizes). When considering only high-quality evidence, similar rates are found (high-quality findings; two studies 34,38 reported significant higher risk, one study 31 mixed, and five findings 31,[35][36][37] no higher risk).…”
Section: Sleep Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, 10 findings were reported, with 2 findings 34,38 showing that children with poor sleep quality are significantly at higher risk (both findings in the direction of poor sleep quality predictive of musculoskeletal pain), one finding 31 showing mixed evidence, and seven findings 31,[35][36][37]39,40 showing no significant higher risk (please see Table 4 for a full description of effect sizes). When considering only high-quality evidence, similar rates are found (high-quality findings; two studies 34,38 reported significant higher risk, one study 31 mixed, and five findings 31,[35][36][37] no higher risk).…”
Section: Sleep Qualitymentioning
confidence: 97%
“…than one article. Three studies were drawn from the Northern Finland Birth Cohort, [31][32][33] while four studies were drawn from a cohort in southern Finland.…”
Section: Study Selectionmentioning
confidence: 99%
“…5 It is thought that the rela tionship is mediated through changes in to show more internalizing behaviors and adolescent boys more externalizing behav iors associated with LBP. These findings support the need to screen for mental and general health status in adolescents pre senting with LBP.…”
mentioning
confidence: 99%
“…Ainda quanto ao avanço da idade, nota-se uma diminuição da quantidade diária de sono (TABELA 3), fato que coloca os escolares de Teutônia em situação de risco, pois tem sido referido, preliminarmente, que quantidades insuficientes de sono (PAANANEN et al, 2010), aliadas ao cansaço, dificuldades em adormecer, acordar no meio da noite, entre outros problemas (AUVINEN et al, 2010), estão associadas às dores musculoesqueléticas.…”
Section: Discussionunclassified